Kajian Filosofis Tradisi Mageburan Di Pura Desa Sekumpul Kecamatan Sawan Kabupaten Buleleng - Nengah Sukmantara; Ida Bagus Wika Krishna (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
The Mageburan tradition is a tradition that is continuously carried out and passed down from generation to generation which is believed by the community to have deep meaning for the Truna-truni and the people of Sekumpul Village. Based on this background, the problems that can be formulated are: 1) The basic foundation of the mageburan tradition at the Sekumpul Village Temple, Sawan District, Buleleng Regency? 2) What is the function of the mageburan tradition at the Sekumpul Village Temple, Sawan District, Buleleng Regency? 3) What are the philosophical values contained in the mageburan tradition at the Sekumpul Village Temple, Sawan District, Buleleng Regency?. The research results obtained are: 1) The basic foundation of the mageburan tradition carried out in Sekumpul Village includes a mythological basis, namely the Magepokan tradition is a myth that has been passed down from generation to generation as a symbol of people's gratitude to God. increase sradha and devotional service. 2) The Mageburan tradition has several functions, namely: a function of purification for the Truna-truni and also the people of Sekumpul Village, the Function of Harmony which in Hinduism is referred to as Tri Hita Karana, the function of rejecting reinforcements for the Truna-truni and the Sekumpu Village community and the function of maintaining culture local village of Sekumpul which has become an ancestral heritage for a long time. 3) Philosophical values contained in the mageburan tradition, namely: ethical values that are implemented from community togetherness and also community obedience in carrying out the mageburan tradition so that this tradition can run smoothly and Tattwa values that can be seen from the implementation of Ngerebeg / Mapurwa Daksina until the end of the implementation of the tradition which contains elements the purity and sincerity of humans in worshiping Ida Sang Hyang Widhi Wasa.